2021
DOI: 10.1371/journal.pone.0254243
|View full text |Cite
|
Sign up to set email alerts
|

Partial restoration of immune response in Hepatitis C patients after viral clearance by direct-acting antiviral therapy

Abstract: Background & aims HCV CD4+ and CD8+ specific T cells responses are functionally impaired during chronic hepatitis C infection. DAAs therapies eradicate HCV infection in more than 95% of treated patients. However, the impact of HCV elimination on immune responses remain controversial. Here, we aimed to investigate whether HCV cure by DAAs could reverse the impaired immune response to HCV. Methods We analyzed 27 chronic HCV infected patients undergoing DAA treatment in tertiary care hospital, and we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…DAA-mediated HCV clearance was associated with the preferential maintenance of memory-like cells [ 85 ]. This is consistent with the fact that DAA treatment results in only partial reversal of T cell exhaustion, whereby proliferative responses are restored but the capacity to produce cytokines or cytotoxicity are not [ 85 , 87 , 88 ].…”
Section: Systems Biology Studies Of the Immune Response During Acute And Chronic Hcv Infectionsupporting
confidence: 80%
“…DAA-mediated HCV clearance was associated with the preferential maintenance of memory-like cells [ 85 ]. This is consistent with the fact that DAA treatment results in only partial reversal of T cell exhaustion, whereby proliferative responses are restored but the capacity to produce cytokines or cytotoxicity are not [ 85 , 87 , 88 ].…”
Section: Systems Biology Studies Of the Immune Response During Acute And Chronic Hcv Infectionsupporting
confidence: 80%
“…In large population-based cohorts treated with DAA and associated with SVR, HCV-related mortality was significantly reduced [ 18 ], though restoration of immune response is only partial [ 19 ] and circulating CD-8 + T cells remain still dysfunctional, especially in advanced chronic liver disease [ 20 ]. After 5 years from SVR, the risk of relapse/reinfection is small, mainly in high-risk patients (HIV associated).…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, IFN family members, especially class I IFN (IFN-α, IFN-β), have important anti-HCC effects[ 32 ]. However, some investigators have suggested that the sudden decrease in viral load caused by DAA treatment causes immune distortion, thus deregulating the antitumor response and releasing precancerous foci from immune surveillance[ 34 , 35 ]. Although it can be explained theoretically, there is little clinical evidence regarding the difference in the HCC risk for patients with DAA-SVR and IBT-SVR.…”
Section: Discussionmentioning
confidence: 99%